Weight status of children and adolescents with autism spectrum disorder: A cross‐sectional analysis of primary care electronic medical records and linked health administrative datasets in Ontario, Canada. - Kinlin, Laura M.; Saunders, Natasha R.; Carsley, Sarah; Keown‐Stoneman, Charles; Tu, Karen; Zwaigenbaum, Lonnie; Birken, Catherine S. (Pediatric Obesity, 2025)
Summary: Background: Individuals with autism spectrum disorder (ASD) may be at increased risk of both obesity and underweight. Objective: To examine the association between ASD and weight status in children and adolescents, adjusting for individual‐ and neighbourhood‐level sociodemographic factors. Methods: We conducted a cross‐sectional study of children and adolescents ≥2 and ≤18 years old using health administrative and demographic data from Ontario, Canada. Using growth measurements from a large primary care database between 2011 and 2016, we categorized weight status using World Health Organization definitions. We defined ASD based on a previously validated algorithm. Results: We included 568 children and adolescents with ASD and 32 967 without ASD. Comparing those with ASD to those without ASD, prevalence of underweight was 3.5% versus 1.9%, overweight 19.0% versus 18.2%, obesity 12.9% versus 7.3%, and severe obesity 5.8% versus 2.2%. In the fully adjusted multinomial logistic regression model, ASD remained associated with underweight (adjusted odds ratio [aOR] 2.02; 95% confidence interval [CI] 1.27–3.20), obesity (aOR 1.87; 95% CI 1.44–2.43) and severe obesity (aOR 2.62; 95% CI 1.81–3.80). Conclusion: Children and adolescents with ASD are at increased risk of underweight, obesity, and severe obesity, independent of sociodemographic characteristics. Strategies addressing growth and weight status are warranted in this population.